Strategic Negotiations: A Theory of Change in Labor-Management Relations - Peterson, Richard B. (Relations industrielles / Industrial Relations, 1995)
The article reviews the book, "Strategic Negotiations: A Theory of Change in Labor-Management Relations," by Richard E. Walton, Joel E. Cutcher-Gershenfeld, and Robert B. McKersie.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Collective bargaining; Labor Unions; Labor negotiations; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z